Evaluation of NeuroPage as a memory aid for people with multiple sclerosis: a randomized controlled trial - Goodwin, Rachel A.; Lincoln, Nadina; das Nair, Roshan; Bateman, Andrew (Taylor & Francis, 2018)
Memory problems are reported in 40-60% of people with multiple sclerosis (MS). These problems affect independence and may limit the ability to benefit from rehabilitation. Our aim was to evaluate the effectiveness of NeuroPage for people with MS living in the community. A multicentre, single-blind randomised controlled crossover trial was conducted. The intervention comprised the NeuroPage service, which sends reminder messages to mobile phones at pre-arranged times. In the control condition participants received “non-memory texts”, that is messages not aimed at providing a reminder, for example supplying News headlines or sport updates. Outcome measures were completed using postal questionnaires after each condition. There were 38 participants, aged 28 to 72 (mean 48, S.D. 11) and 10 (26%) were men. There were no significant differences between NeuroPage and control conditions on the Everyday Memory Questionnaire (p=0.41, d=0.02). The number of daily diary items forgotten in the NeuroPage condition was significantly less than in the control (9% vs. 31%, p=0.01, d=-0.64). Psychological distress was less in the NeuroPage condition than control (p=0.001, d=-0.84). Further evaluation of the effect on everyday memory is required.